2018
DOI: 10.1007/s00520-018-4468-7
|View full text |Cite
|
Sign up to set email alerts
|

Grandparents of children with cancer: a controlled comparison of perceived family functioning

Abstract: The detrimental impact of childhood cancer likely extends beyond the immediate family members. Including grandparents in interventions-beginning at diagnosis-to reduce distress and increase cohesion for families of a child with cancer is warranted, particularly for grandparents who provide care to their sick grandchild or siblings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
0
18
0
2
Order By: Relevance
“…Families experience enormous upheaval when a child is diagnosed with cancer 1‐4 . Along with the physical and psychological effects of childhood cancer, families also face challenging impacts on finances and employment.…”
Section: Introductionmentioning
confidence: 99%
“…Families experience enormous upheaval when a child is diagnosed with cancer 1‐4 . Along with the physical and psychological effects of childhood cancer, families also face challenging impacts on finances and employment.…”
Section: Introductionmentioning
confidence: 99%
“…A literatura indica que os avós sofrem de forma multiplicada e emudecida quando um de seus netos adoece. (15)(16)(17)(18) Os avós carecem de suporte, mas não o encontram na equipe multiprofissional, temem sobrecarregar os filhos com suas demandas e, diante disso, abafam o próprio sofrimento para tentarem ajudar a família do filho da melhor forma possível. (15,17,18) Os discursos dos participantes deste estudo, tanto sobre experiências vividas quando crianças quanto sobre o que testemunharam nas atividades práticas, trazem aspectos semelhantes de sofrimento e falta de suporte oferecido aos avós.…”
Section: Discussionunclassified
“…Based on an exhaustive literature review, a list of 10 topics constituting potential areas of need in parents of children with cancer was devised [ 3 , 10 , 20 , 23 , 24 , 25 ]. From there, ad hoc interview questions were considered (see Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to informational support, parents commonly require social support, both informal—from family members, including grandparents and siblings [ 25 ]—and formal (health personnel, bosses, etc.). It has been demonstrated that perceived social support provides health and well-being benefits [ 19 , 26 ].…”
Section: Introductionmentioning
confidence: 99%